DISCOURSE ANALYSIS IN THE FIELD OF TAX AND TAXATION (American Journal of Research in Humanities and Social Sciences, 2022)
The tax system plays an important role in the development of the country's economy. Therefore, the introduction of an effective tax system in the country is one of the most important issues. In this regard, in recent years in the country, as in all areas, a number of measures have been taken to reform the tax system, reforms to reduce the tax burden, and a number of measures to improve the system of taxation of business activities. This article reflects the views of the authors on the ongoing reforms of the tax system in the country, tax debt, and its elimination.